Chaos, Wahnsinn : Permutationen der zeitgenössischen Kunst - Denk, Wolfgang; Fabro, Luciano; Gachnang, Johannes; Grob, Markus; Harlizius-Klück, Ellen; Hess, Ewa; Kristeva, Julia; Meyer, Eva; Schmitz, Rudolf; Seitter, Walter; Tobler, Konrad (Krems : Kunsthalle Krems, 1996)
Abraham, Raimund ; Absalon, Hildegard ; Arp, Hans (Jean) ; Baselitz, Georg ; Broodthaers, Marcel ; Brouwn, Stanley ; Fabro, Luciano ; Federle, Helmut ; Förg, Gunther ; Hirst, Damien ; Immendorff, Jörg ; Kawamata, Tadashi ; Kiecol, Hubert ; Kirkeby, Per ; Kogler, Peter ; Lane, Abigail ; Lohse, Richard Paul ; Lüpertz, Markus ; Meyer-Amden, Otto ; Nauman, Bruce ; Nitsch, Hermann ; Penck, A.R. ; Pettibon, Raymond ; Polke, Sigmar ; Rainer, Arnulf ; Sacconi, Marie ; Schwitters, Kurt ; Soutter, Louis ; Taeuber-Arp, Sophie ; Toroni, Niele ; Weiner, Lawrence ; West, Franz ; Wölfli, Adolf
biog. p. 181-196
Duits
Chaos, Wahnsinn : Permutationen der zeitgenössischen Kunst, Kunsthalle Krems, 20. Juli - 17. October 1996
boek